Contrasting Pediatric and Adult Methicillin-resistant Staphylococcus aureus Isolates - Michael Z. David; Susan E. Crawford; Susan Boyle-Vavra; Mark A. Hostetler; Daniel C. Kim; Robert S. Daum (Emerging Infectious Diseases, 2006)
We performed a prospective study of all inpatient and outpatient methicillin-resistant Staphylococcus aureus (MRSA) isolates identified at the University of Chicago Hospitals from November 2003 through November 2004. Differences in resistance to non–β-lactam antimicrobial drugs were determined after stratification of the 578 MRSA isolates into 4 groups by patient age (pediatric vs. adult) and onset location (community vs. hospital). Non–β-lactam resistance was significantly greater among the 288 adult than the 177 pediatric community-associated isolates for erythromycin (93.2 vs. 87.0%, p = 0.03), clindamycin (51.8 vs. 7.3%, p<0.001), ciprofloxacin (62.1 vs. 10.7%, p<0.001), gentamicin (11.1 vs. 1.1%, p<0.001), and tetracycline (19.9 vs. 6.4%, p<0.001). In contrast, hospital-associated MRSA isolates from children and adults had similar rates of non–β-lactam antimicrobial drug resistance. In our region, clindamycin is an appropriate empiric therapy of community-associated MRSA infection in children but should be used with caution in adults.